A Neonatal Mouse Model for Pressure Overload: Myocardial Response Corresponds to Severity - Gu, Jielei; Chen, Xuke; Jin, Yangshuo; Liu, Mingke; Xu, Qiong; Liu, Xiaolin; Luo, Zhenyu; Ling, Sisi; Liu, Ningning; Liu, Shiming (Frontiers in Cardiovascular Medicine, 2021)
The heart regeneration after apical resection and myocardial infarction in neonatal mice has been studied for years. However, the response of neonatal mouse heart under pressure overload is seldom explored. This study aimed to induce pressure overload in neonatal mice through a transverse aortic constriction (TAC) with different-gauge needles so as to investigate the effect of pressure overload on cardiomyocyte proliferation and hypertrophy in these mice. Myocardial hypertrophy was evaluated by echocardiographic, pathological, and molecular analyses. Cardiomyocyte proliferation was detected by immune-staining of phospho-histone H3, Ki67, and 5-bromo-2-deoxyuridine. Mild pressure overload induced with a 30-gauge needle stimulated cardiomyocyte proliferation, adaptive hypertrophy, and angiogenesis. The heart function was not hampered even 21 days after the surgery. Moderate pressure overload induced with a 32-gauge needle led to pathological myocardial hypertrophy, fibrosis, and heart failure 7 days after the surgery. The gene and protein expression levels of markers of hypertrophy and fibrosis increased in 32-gauge TAC group compared with that in sham and 30-gauge TAC groups. The mice barely survived after severe pressure overload induced with a 34-gauge needle. The findings of this study might provide new insights into cardiomyocyte proliferation and hypertrophy in neonatal mice under pressure overload.